2018
DOI: 10.26444/aaem/85589
|View full text |Cite
|
Sign up to set email alerts
|

Skin and nasal vestibule colonisation by Staphylococcus aureus and its susceptibility to drugs in atopic dermatitis patients

Abstract: Introduction. Atopic dermatitis (AD) is a chronic and recurrent disease with an inflammatory background. Genetic and environmental factors are responsible for the occurrence and development of this dermatosis. Objective. The aim of the study was to assess the frequency of colonisation of the nasal vestibule and apparently healthy skin by S. aureus, and to assess dermal lesions for superinfection with S. aureus in AD patients. Materials and method. The research was performed on a population of 100 AD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…10,33 With respect to sampling site-speci c colonisation, AD-lesional skin has been shown to be more susceptible to S. aureus colonisation compared to AD-uninvolved, non-lesional skin, with a reported prevalence of colonisation of 23-70% vs. 6-39%. 10,34,35 Similarly, we noted higher frequency of colonisation on lesional skin compared to non-lesional skin among urban cases, but not in rural cases. Further, similar colonisation rates on lesional skin and anterior nares have been reported in AD with nasal colonisation thought to be the main source of the increased skin colonisation in AD.…”
Section: Discussionsupporting
confidence: 66%
“…10,33 With respect to sampling site-speci c colonisation, AD-lesional skin has been shown to be more susceptible to S. aureus colonisation compared to AD-uninvolved, non-lesional skin, with a reported prevalence of colonisation of 23-70% vs. 6-39%. 10,34,35 Similarly, we noted higher frequency of colonisation on lesional skin compared to non-lesional skin among urban cases, but not in rural cases. Further, similar colonisation rates on lesional skin and anterior nares have been reported in AD with nasal colonisation thought to be the main source of the increased skin colonisation in AD.…”
Section: Discussionsupporting
confidence: 66%
“…At present, mechanistic evidence suggests that S. aureus is mutually promoted by and aggravated by Th2-mediated inflammation and skin barrier impairment in AD [ 10 , 35 ]. However, previous studies that evaluated the efficacy of topical antibiotics showed conflicting results [ 36 , 37 ], and it has been hypothesized that this may be due to recolonization by nasal S. aureus and eradication of beneficial bacteria [ 38 , 39 ]. Ongoing research is working with manipulating the skin microbiome in the therapeutic management of AD [ 40 , 41 ], and initial pilot trials showed that topical application of coagulase negative staphylococci (CoNS) [ 40 ] and Roseomonas mucosa [ 42 ] decreased disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…85 A study sampling S aureus from both children and adults revealed that 85% of the subjects were colonized with S aureus in the nares and approximately 77% of the subjects with AD colonized by S aureus in the nares were also colonized on the skin. 86 These findings suggest that S aureus proliferates in the nasal cavity and a connection exists between the biomes at these 2 surfaces.…”
Section: Allergic Rhinitismentioning
confidence: 90%